A (un) Assessment of Physicochemical, Microbial, and Hygienic Quality of Raw Cow Milk Produced in Dairy Herds from the Peruvian Andes - Fernando Arauco Villar; Leonor Guzmán Estremadoyro; Rafael Pantoja Esquivel; Noemí Mayorga Sánchez; Ide Unchupaico Payano; Alex Huamán De La Cruz (La Granja: Revista de Ciencias de la Vida)
The study was performed in Mantaro Valley, Junín, Perú, with the aim to evaluate the physicochemical, microbial, and hygienical quality of 40 raw cows’ milk collected from dairy herds from four provinces: Huancayo (n = 13), Concepción (n = 11), Jauja (n = 9), and Chupaca (n = 7). Physicochemical properties were quantified by evaluating the fat content, density, non-fat-solids, protein, water add, freezing point, salts, total solids, lactose, and pH using the milk analyzer Lactoscan SP. Microbial quality was determined through viable mesophilic bacteria (VMB), total coliforms (TC), fecal coliforms (FC), and yeast and mold (YMC). In addition, antibiotic presence was measured by SNAPduo*ST plus test kit and Reduction time by Methylene Blue Dye Reduction (MBRT). The results found in this work indicate that physicochemical features of raw cow milk were adequate compared to standard levels. In microbial quality, only Chupaca showed higher values (6.28 log cfu/mL) than recommended (5.3 log cfu/mL). Likewise, total bacterial/mL in Huancayo (H, 19.12 × ) and Concepcion (C, 1.18 × ) were relatively high concerning the acceptable level (1×  bacteria/mL of raw milk). Antibiotic presence was found in 37.5 % (n = 15) from the total of samples (n = 40). MBRT analysis reported 32.5 %, 45.0 %, and 22.5 %, as of excellent, good, and acceptable quality, respectively. Thus, it was concluded that physicochemical properties presented an appropriate level whereas microbial quality in the areas was good but is recommendable for enriched hygienic practices, personal hygiene in milk handling due to microbial presence, and educating the public on safety issues.